Effect of thiobencarb and butachlor on photosynthesis, carbohydrate content, and amylase and protease activity in rice (Oryza sativa) and barnyard grass (Echinochloa crus-galli - KUMAR, JITENDER; JAIPRAKASH, JAIPRAKASH (The Indian Journal of Agricultural Sciences, 2013)
A pol experiment was conducted during 1989 to study the effect of thiobencarb and buta chlor on pholosynithesis and carbohydrates in rice (Oryza sativa L.) and barnyard grass (Echinochloa crus.galli (L.) P. Beauv.] plants raised alone and in combination with each other. Besides, the activity of amylase and protcase was studied. in seedlings raised in petri-dishe kept in an incubator. Stomatal conductance and CO2concentration along with photosynthcsis and carbohydrate content of leaves were recorded at 15, 30, 45 and 60 days after transplanting rice and sowing the seeds of barnyard grass. These were treated with 0,1.5. 3.0 and 4.5 kg/ha thiobcncarb and butachlor separately. The concentrations of herbicides in petri-dishes were 0, 25, 50 and 75 ppm and enzymes were assayed at 24.78,72 and 96 hr after sowing. The herbicides did not allow barnyard grass to geminale in pots. Crop-weed association did not affect stomatal conductance. total carbohydrates, starch and reducing sugars in leaves but decreased the photosynthesis of the grass. The herbicides did not reduce these factors in rice leaves. In barnyard grass the rate of photosynthesis was more, though ita internal CO2 concentration and stomatal conductance was low. The herbicides reduced the alpha-amylase activity with increase in concentration. Sharp increase in alpha-amylaseactivity was observed at 96hr in both the species. Protease activity was maximum at 48 hr in rice and at 24 hrin barnyard gran. Both the herbicides reduced the proteasc activity at 25 ppm but increased it at 75 ppm in both the species.